Psychophysical assessment of the affective components of non-painful touch - Essick, G K; James, A; McGlone, F P (Neuroreport, 1999)
A novel psychophysical procedure for the evaluation of the affective components of touch was developed. A fabric material was stroked across the test site at a controlled direction and velocity, after which the subject provided a numerical estimate of pleasantness. Significant differences were detected for the sites tested (FACE vs ARM), the fabric materials used (VELVET, COTTON and PLASTIC MESH), and the velocity of motion (0.5, 5 and 50 cm/s). Attesting to their validity, estimates of pleasantness correlated negatively with estimates of unpleasantness obtained for the same stimuli. Moreover, subjects were reasonably consistent in their ratings upon stimulus replication. These findings demonstrate that the hedonic qualities of touch can be psychophysically evaluated, and that valid and reliable estimates are obtained.